A SUCCESS ANALYSIS OF SIDODADI-SABARA ROAD DEVELOPMENT PROJECT IN SEMARANG CITY FOR THE FISCAL YEAR 2019 - Affendi, Achmad Sholikin; Mudiyono, Rachmat; antonius, antonius (Pondasi, 2023)
Economic growth in a country, especially in big cities such as Semarang Indonesia, has an impact to an increase in the number of vehicles passing through the area. This issue logically correlates to why the existing transportation facilities and infrastructure need to continuously improve. Semarang Public Works Department of Bina Marga as an extension of the central government has been continuously making efforts, including improving the quality and quantity of road sections in the areas deemed to need handling. These aim to expediting and accelerating traffic activities among regions. Using quantitative methods supported by SPSS V26 software, this study aimed (1) to investigate factors influenced the success of Sidodadi Sabara project, (2) to find out factors which most influenced the success of the project, and (3) to find out how successful the project was. From results of the analysis, it was recognized that the work management be the most dominant factor among the other factors. By anticipating this variable, the success rate of Sidodadi Sabara road project development would potentially increase. This research was expected to be an empirical input for related parties, especially the implementing agencies of the project.